Intrastriatal Administration of Exosome-Associated Pathological Alpha-Synuclein Is Not Sufficient by Itself to Cause Pathology Transmission - Karampetsou, Mantia; Sykioti, Vasia Samantha; Leandrou, Emmanouela; Melachroinou, Katerina; Lambiris, Alexandros; Giannelos, Antonis; Emmanouilidou, Evangelia; Vekrellis, Kostas (Frontiers in Neuroscience, 2020)
α-Synuclein (α-syn) has been genetically and biochemically linked to the pathogenesis of Parkinson’s disease (PD). There is accumulating evidence that misfolded α-syn species spread between cells in a prion-like manner and seed the aggregation of endogenous protein in the recipient cells. Exosomes have been proposed to mediate the transfer of misfolded α-syn and thus facilitate disease transmission, although the pathological mechanism remains elusive. Here, we investigated the seeding capacity of exosome-associated α-syn, in vivo. Disease-associated α-syn was present in exosome fractions isolated from transgenic A53T mouse brain. However, following intrastriatal injection of such exosomes in wild-type (wt) mice, we were not able to detect any accumulation of endogenous α-syn. In addition, recombinant fibrillar α-syn, when loaded to isolated brain exosomes, induced minor pathological α-syn brain accumulation at 7 months post injection. These data suggest that exosomes neutralize the effect of toxic α-syn species and raise additional questions on their paracrine modulatory role in disease transmission.